2020
DOI: 10.3389/fphar.2020.01266
|View full text |Cite
|
Sign up to set email alerts
|

NCS 613, a Potent PDE4 Inhibitor, Displays Anti-Inflammatory and Anti-Proliferative Properties on A549 Lung Epithelial Cells and Human Lung Adenocarcinoma Explants

Abstract: Chronic inflammation is a deleterious process occurring in several pulmonary diseases; it is a driving force promoting tumorigenesis. By regulating local cyclic nucleotide concentration, cyclic nucleotide phosphodiesterases (PDE) govern important biological processes, including inflammation and proliferation. The aim of this study was to investigate the anti-inflammatory and anti-proliferative effects of NCS 613, a specific PDE4 inhibitor, on TNFa-treated human lung adenocarcinoma cell line (A549) and on human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…In addition, an overdose FA injection induced the activation of the MAPK pathway, which is the main target involved in the protective effect on FA-induced AKI (Jiang et al, 2016). A recent study reported that NCS613, another potent PDE4 inhibitor, was a negative modulator of p38 phosphorylation that exerts anti-inflammatory effects on TNF-α-treated lung epithelial cells by inhibiting the activation of the MAPK signaling pathway (Yougbare et al, 2020). Moreover, some studies have suggested that the MAPK signaling pathway mainly contributes to cell pyroptosis, which further drives massive inflammation (Yao and Sun 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, an overdose FA injection induced the activation of the MAPK pathway, which is the main target involved in the protective effect on FA-induced AKI (Jiang et al, 2016). A recent study reported that NCS613, another potent PDE4 inhibitor, was a negative modulator of p38 phosphorylation that exerts anti-inflammatory effects on TNF-α-treated lung epithelial cells by inhibiting the activation of the MAPK signaling pathway (Yougbare et al, 2020). Moreover, some studies have suggested that the MAPK signaling pathway mainly contributes to cell pyroptosis, which further drives massive inflammation (Yao and Sun 2019).…”
Section: Discussionmentioning
confidence: 99%
“…PDE4 inhibitors have cytotoxic effects on A549 lung cancer cells ( 27 ), and PDE4 is a key regulator of normal and cancer epithelial cell proliferation. PDE4 may thus be effective for the treatment of chronic inflammation and cancer cell proliferation ( 28 ). The role of PDE4B as a prognostic and therapeutic target, however, differs between specific tumors.…”
Section: Discussionmentioning
confidence: 99%
“…In other study, it has been shown that PDE4 inhibitors improve kidney damage by increasing cAMP levels after renal ischemia-reperfusion injury in rats 32 . Our recent study has shown that PDE4 inhibition by NCS 613 exerts antiproliferative effects on A549 lung epithelial cells and human lung adenocarcinoma explants, as well as anti-proliferative effects on mesangial cells 29,33 . From animal studies to patient bed site, our translational observations strongly support the idea that inhibition of PDE4 activities in peripheral mononuclear cells (PBMCs) can control proinflammatory signaling.…”
Section: Pde4 the Major Camp Degrading Enzyme In Lupus Nephritismentioning
confidence: 98%
“…NCS 613 is a new potent PDE4 inhibitor which exerts anti-inflammatory properties (Figure 1). Oral administration of NCS 613 reduces neutrophil recruitment in lipopolysaccharide (LPS)-treated mouse bronchi as and abolishes hyperresponsiveness of cultured human bronchi [27][28][29] . Recently, we reported that NCS 613 suppresses systemic inflammation and immunes complexes deposition in kidney of lupus prone mice 30 .…”
Section: Pde4 the Major Camp Degrading Enzyme In Lupus Nephritismentioning
confidence: 99%